The Use of Slang in Youtube Comments - Faishal Arkan; Ahmad Tafuzu Fahmi M (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
This research in title “The Use of Slang in Youtube Comments". The problems of this research are: What kinds of slang used by the netizens comment in youtube account. The researcher used descriptive qualitative method. The purpose of this research is to know slang language that is used on comment in Youtube. In collecting data, the writer concentrates the utterance‟s which contains the slang by the netizens comment in Youtube account . The result of the research, there are 4 slang type that are used by the netizens is affective meaning, social meaning, and connotative